2016
DOI: 10.1177/0961203316651743
|View full text |Cite
|
Sign up to set email alerts
|

The caregiver burden in lupus: findings from UNVEIL, a national online lupus survey in the United States

Abstract: Caregiving for patients with lupus has a substantial impact on the work productivity and the social and emotional functioning of caregivers. Healthcare professionals and policymakers should continually assess the impact of healthcare decisions on the well-being of those caring for patients with lupus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…18 19 In 2010, 4 69.5% reported that lupus had affected their career versus 65.8% in 2020; of those, 29.4% reported the need to work flexible hours in 2010 versus 31.9% in 2020. Similar results have been shown in large US studies, [20][21][22] also showing a relationship between disease activity and work productivity loss, as well as with activity impairment. This yielded generally high levels of anxiety about the future in this survey.…”
Section: Impact Of Sle On Studies Work and Family Lifesupporting
confidence: 89%
“…18 19 In 2010, 4 69.5% reported that lupus had affected their career versus 65.8% in 2020; of those, 29.4% reported the need to work flexible hours in 2010 versus 31.9% in 2020. Similar results have been shown in large US studies, [20][21][22] also showing a relationship between disease activity and work productivity loss, as well as with activity impairment. This yielded generally high levels of anxiety about the future in this survey.…”
Section: Impact Of Sle On Studies Work and Family Lifesupporting
confidence: 89%
“…6 Only three other studies, all performed in the USA, have assessed the impact of SLE on carers; all of these studies involved relatively small carer numbers ( N = 6, 10 and 253). 7,14,15 An additional limitation was that our survey was mainly limited to Caucasian and computer literate participants with the time to answer the survey; thus, it may not be representative of all SLE patients in the UK. There may also have been carer selection bias, with only carers who felt particularly burdened completing the survey.…”
Section: Discussionmentioning
confidence: 99%
“…No cure exists for SLE, and the burden of illness is high for patients and carers. 57 Patient-oriented research on the burden of SLE would help further understanding of how outcomes in patients with SLE could be improved. Questionnaires measuring patient-reported outcomes (PROs), such as fatigue and health-related quality of life (HRQoL), provide valuable information about the burden of a disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UNVEIL survey, conducted in 2014 in a partnership with the Lupus Foundation of America, examined the burden of SLE for patients and their caregivers in the US [ 13 – 14 ]. In 2019, the partnership conducted a further survey—SLE-Understanding Preferences, Disease Activity, and Treatment Expectations (SLE-UPDATE)—to provide detailed information on patient experiences, satisfaction, and expectations with current SLE treatment.…”
Section: Introductionmentioning
confidence: 99%